ELT TEXTBOOKS IN INDONESIA: A COMPARATIVE STUDY OF NATIONAL AND INTERNATIONAL CURRICULA - Nora Nopikasari; Ira Maisarah (Wiralodra English Journal, 2026)
This research compares the coverage of language skills, types of learning tasks, and curriculum conformity between two English textbooks (Oxford International Primary English, an international textbook, and My Next Words, a nationally developed textbook for third-grade students in Indonesian classrooms). Using a qualitative content analysis methodology, the investigation examines how each textbook systematically construes language skills, task design, and curricular coherence. The results show that the content in the national textbook has focused heavily on basic literacy skills, repetition, and the incorporation of local cultural themes. However, it offers few opportunities for communicative language use, problem-solving, and higher cognitive functions. Meanwhile, the international textbook reflects a more balanced integration of the four language skills, inquiry types, project-based learning tasks, and global issues to enhance learners’ understanding. The findings of the study indicate that a national English language teaching material can be improved by adding local content, authentic texts, an intercultural perspective, and communicative project work. The research also highlights significant implications for curriculum designers, textbook writers, and teacher education institutions that aim to enhance the overall quality of English language teaching in the Indonesian context.